MOLECULAR IDENTIFICATION OF SOME APHID SPECIES (HOMOPTERA; APHIDIDAE) BASED ON RFLP-PCR TECHNIQUE - Hero Muhammad; Dilzar Mawlud; Kamaran Taha; Nabeel Mawlood (Mesopotamia Journal of Agriculture)
This work includes, identification eight species of Aphids (Homoptera: Aphididae) which collected from the leaves of different plants in many localities of Erbil governorate Kurdistan region-Iraq from the period May till July 2022, these are: Chaitophorus salijaponicus, Aphis fabae, Macrosiphum rosae, Capitophorus carduinus, Myzus persicae, Aphis ruborum, Aphis punca, and Aphis gossypii. The mitochondrial cytochrome C Oxidase subunit I (COI) gene used for identification these species. DNA was isolated, and a band of 550 bp of mt COI gene was amplified during the PCR amplification. The amplicons were digested with HinfI and DdeI restriction enzymes. The restricted fragments produced by RFLP technique were proved by agarose gel electrophoresis. The results illustrated that digested amplicons were given bands according to their cut sites. This study presented that studying aphids to detect their species through a RFLP-PCR technique by using these restriction enzymes can distinguish some species with reliable results. HinfI and DdeI REs could not distinguish all species, HinfI only discriminated species Macrosiphum rosae, Capitophorus carduinus, Myzus persicae and Aphis gossypii, but DdeI identified the remain species, Chaitophorus salijaponicus, Macrosiphum rosae, Myzus persicae and Aphis ruborum,within and among other species exactly. The study suggested using other restriction enzymes to provide full recognition profile for all species.